Digital Fabrication for Cultural Heritage Enhancement: A Tale of Three Projects - Nguyen, Quang Huy; Tramontin, Marialetizia; Belvedere, Marianna (Mimesis Journal, 2024)
Technologies of digital fabrication (DF) facilitate methods to form the physical reproductions from 3D digital models. In recent decades, we have seen a vast development of those technologies, which have surpassed traditional methods because of fast replicability, flexible scalability, and data digitability. In the field of cultural heritage (CH), because of the ability to enhance the authenticity of antiquities, human-centric and experience museum design are now considered as effective tools of information delivery. The goal of the article is to create a common workflow for applying digital fabrication in three cases and assess their effectiveness through context, objectives, technologies used, inclusivity and accessibility, interactivity, and narrativity.